العوالم الأخرى في تصورات الأدباء دراسة مقارنة - توفي, عمر ابراهيم (Sulaimani Journal for Humanities, 2001)
The present paper is concerned with the conception of well- bred writers about the other cosmos including Hell and Heaven to disclose the nature of human rationality , imagination and dogmatic views . The paper dealt with the Egyptian and Babylonian myths , what is mentioned in the tales of messengers , on Edris ( peace be upon him ) , Elyatha and Odyssey of Homer particularly what is relevant to Heaven , advocacy and the lower cosmos . In anther section we have dealt with Aristovan’s play entitled (Frogs) due to the critical and literary views that can be found in it . next to this virgil's ( Enyatha ) is dealt with in particular the scenes with show human groups in the doomsday . In addition to this , the researcher didn't ignore the wise Zoroastor and his opinions on Heaven and Hell . Among the Islamic heritage , the paper tackled the attitude of the seal prophets and his influence on the forthcoming tasks . Moreover , the mystic's letters , the " Divine Comedy " are also dealt with . Besides , the paper talks about Ibn-shahid's " Dependencies and Hurricanes " and his conception about goblin world . Al-waharani's book on the Day of congregation is tackled as well . The paper ends in something about poem by Abdl-Rahman Shukri and his conception of the Day of Resurrection.